The effectiveness of Music Hearing learning Outcomes of Higher Education Chinese Students - Zhang, Yali (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study focuses on the effectiveness of music majors using EarMaster software for music hearing training. The research objectives are as follows: 1. To determine whether using music learning software can improve the learning effect of hearing training; 2. Determine the difference in learning effect between the use of learning software and the use of traditional learning methods; 3. Determine students’ learning attitude towards music hearing training by using music learning software. Research design, data, and methodology: A quasi-experiment and questionnaire survey were used. A total of 192 students were selected using the purposive sampling method. Music perception, analysis, and reproduction ability were tested in an eight-week quasi-experiment. Through a questionnaire survey, the perceived ease of use, perceived usefulness, and learning attitude towards the software use were investigated. Results: After the experimental intervention, the students in the experimental group improved significantly higher than the control group in music perception, analysis ability, reproduction ability, and total score on hearing test. Conclusions: The method of using music learning software significantly improves the hearing ability of music majors compared with the traditional learning method. The research has a specific value to the practice of listening and learning for music majors.